Alterations in PTEN, MDM2, TP53 and AR protein and gene expression are associated with canine prostate carcinogenesis - Rivera-Calderón, Luis Gabriel [UNESP]; Fonseca-Alves, Carlos Eduardo [UNESP]; Kobayashi, Priscila Emiko [UNESP]; Carvalho, Marcio [UNESP]; Drigo, Sandra Aparecida [UNESP]; de Oliveira Vasconcelos, Rosemeri [UNESP]; Laufer-Amorim, Renée [UNESP] (Elsevier, 2016)
The PTEN, AR, MDM2 and p53 protein network plays a central role in the development of many human cancers, thus eliciting the development of targeted cancer therapeutics. Dogs spontaneously develop tumours, and they are considered a good model for comparative oncology initiatives. Due to the limited information on these proteins in canine tumours, this study aimed to investigate gene and protein alterations in PTEN, AR, MDM2 and p53 in canine prostate cancer (PC). Protein expression was evaluated by immunohistochemistry (15 normal, 22 proliferative inflammatory atrophy (PIA) and 19 PC samples) and Western blotting (2 normal prostate tissue, 2 BPH, 2 PIA samples and 2 PC samples) and gene expression by RT-qPCR (10 normal, 10 PIA and 15 PC samples) of formalin-fixed tissue. We identified nuclear and cytoplasmic expression of PTEN and p53 in all samples, with only nuclear staining found for MDM2 and AR. Our results revealed high expression of MDM2 in PC and PIA samples compared to normal samples, whereas PTEN, P53 and AR expression was down-regulated in PC compared to normal tissue. All tumour samples (n = 19) showed loss of nuclear PTEN expression, and all cancer mimickers showed positive nuclear staining. Therefore, nuclear PTEN staining could be a good diagnostic marker for differentiating between malignant lesions and mimickers. Canine prostate carcinogenesis involves increased expression of MDM2 in association with decreased expression of PTEN, p53 and AR, such as occurs in hormone refractory PC in men. Thus, dogs may be an important model for studying advanced stage PC.
Keywords: Dog; Formalin-fixed tissue; Gene expression; Immunohistochemistry; Prostatic disease